2017
DOI: 10.3390/ijms18081680
|View full text |Cite
|
Sign up to set email alerts
|

Various Mechanisms Involve the Nuclear Factor (Erythroid-Derived 2)-Like (NRF2) to Achieve Cytoprotection in Long-Term Cisplatin-Treated Urothelial Carcinoma Cell Lines

Abstract: Therapeutic efficacy of cisplatin-based chemotherapy for advanced-stage urothelial carcinoma (UC) is limited by drug resistance. The nuclear factor (erythroid-derived 2)-like 2 (NRF2) pathway is a major regulator of cytoprotective responses. We investigated its involvement in cisplatin resistance in long-term cisplatin treated UC cell lines (LTTs). Expression of NRF2 pathway components and targets was evaluated by qRT-PCR and western blotting in LTT sublines from four different parental cells. NRF2 transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 92 publications
(123 reference statements)
0
19
0
Order By: Relevance
“…Four cisplatin-resistant LTT sublines were generated from the UCCs RT-112, J82, 253J, and T-24 [ 16 , 33 ]. Resistance was quantified by determination of IC 50 values following 72 h cisplatin treatment, which were between 10-fold and 21-fold increased compared to their parental controls ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four cisplatin-resistant LTT sublines were generated from the UCCs RT-112, J82, 253J, and T-24 [ 16 , 33 ]. Resistance was quantified by determination of IC 50 values following 72 h cisplatin treatment, which were between 10-fold and 21-fold increased compared to their parental controls ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, we have previously reported that several other factors involved in cisplatin and glutathione metabolism, which are NRF2 targets, are also upregulated to different extents in the LTT lines, most prominently in RT-112-LTT and T24-LTT [ 16 ]. These data indicate that a number of different pre-target factors are implicated to various extents in cisplatin resistance in different sublines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The response and resistance of cancer cells to chemotherapy and hyperthermia depend on the induction and expression of a number of cytoprotective proteins, including Hsp70 and Hsp27 (17)(18)(19). Therefore, the modulation of cytoprotective proteins may serve a crucial role in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%